1975
DOI: 10.1111/j.1432-1033.1975.tb04150.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes of Alamethicin Induced by Solvent and Temperature

Abstract: I3C nuclear magnetic resonance (NMR) and circular dichroism (CD) have been used for studies on the conformation of alamethicin. The 13C NMR spectrum is assigned with the aid of signals of synthetic partial sequences and selective proton decoupling. The solvent and temperature-dependence of the I3C NMR spectra, TI measurements and the use of lanthanide-shift reagents allow the differentiation between the amino acids belonging to a rigid a-helical portion of the alamethicin sequence and those belonging to a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
39
0
7

Year Published

1977
1977
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(53 citation statements)
references
References 48 publications
7
39
0
7
Order By: Relevance
“…1). The former, proposed by Payne et al (19), has been confirmed by Ovchinnikov et al (20), while the latter, proposed by Martin and Williams (21,22), found the support of the Jung group (17 ALA-o, on the other hand, the same side group is engaged in an amide bond with phenylalaninol and the imino function of Pro2 is blocked by an Ac-Aib residue. Gln'9 again is identical in both sequences and provides the a-carboxyl group that makes ALA a monobasic acid.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…1). The former, proposed by Payne et al (19), has been confirmed by Ovchinnikov et al (20), while the latter, proposed by Martin and Williams (21,22), found the support of the Jung group (17 ALA-o, on the other hand, the same side group is engaged in an amide bond with phenylalaninol and the imino function of Pro2 is blocked by an Ac-Aib residue. Gln'9 again is identical in both sequences and provides the a-carboxyl group that makes ALA a monobasic acid.…”
supporting
confidence: 66%
“…First, in partial hydrolysates of ALA, a peptide comprising -Glu(y-Pro)-, the cycle-forming link, was not found (19). Second, the presence of blocking groups on the Glul' y-carboxyl (phenylalaninol) and the Pro2 imino group (Ac-Aib) was demonstrated (21,22,17), thus precluding a direct covalent link between these two residues. On these grounds, the synthesis of ALA-o rather than ALA-c was undertaken first.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, the torsional angles, 4~ for Ala 6, Gln 7 and Val 9 are in the correct range for a helix (60°). From CD studies in methanol [13], it was estimated that 40% of the ALA backbone was in a helix. This degree of helicity is consistent with the observation that the 8 NHs in the segment from Aib3-Aib 1° exchange 'very slowly', and that residues 6, 7 and 9 have helical Q-values.…”
Section: Discussionmentioning
confidence: 99%
“…aH-NMR studies of partially purified Ala at 270 MHz [5] were instrumental in establishing its open-chain structure and the presence of the hitherto unsuspected phenylalaninol residue (see also [ 13]). The extent to which the spectra could be analyzed was limited by the low field and low resolution.…”
Section: Discussionmentioning
confidence: 99%